The Effect of Audio Stimuli in Gastronomic Establishments - Ivana ONDRIJOVÁ; Dávid MIŠKO (Communications of International Proceedings, 2024)
In gastronomic establishments, audio stimuli such as music and noise play a key role in shaping the overall atmosphere and customer experience. These sound elements can significantly influence customers' emotions, behavior, and satisfaction levels. The primary aim of this paper is to examine how customers perceive audio stimuli in gastronomic establishments, with a focus on gender as a factor to explore possible perceptual differences between men and women. The research sample consisted of 138 respondents. The results indicate that there are no statistically significant differences between men and women in evaluating audio stimuli in gastronomic establishments. However, there are specific differences, where music is more effective in improving women's mood than men's. On the other hand, the noise from children in a gastronomic establishment bothers women more than men.
Keywords: gastronomic establishment; marketing; customer behavior; auditory marketing